Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

kassey1329

  • 3 years ago

Solve: 3(3t + 3) = 3(-3t + -39)

  • This Question is Closed
  1. timo86m
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    distribute out the 3's in both sides then it should be simpler or cancel out the 3 by dividing both sides by 3. THis one is easier I think.

  2. catsrule332
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    9t+9=-9t - 117. 18t + 9 = -117. 18t=-126. t=-126/18 t=-7

  3. timo86m
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    or if you cancaled out the 3s 3t+3=-3t+-39

  4. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy